Ecotoxicological assessment of sediments from the Port of Santos and the disposal sites of dredged material (Brazilian Journal of Oceanography, 2007)
The dredging of sediments from the Santos Channel is necessary to allow the navigation of ships operating in the Port of Santos. The disposal sites for such sediments are situated on the coastal zone, in front of the Santos Bay. The present paper aimed at evaluating the toxicity of sediments collected at the Santos Channel and at the former and current sediment disposal sites. Whole sediment tests with amphipods and elutriate assays with sea-urchin embryos were used. The samples from the Santos Channel were considered the most toxic: all the sediment samples from this area showed toxicity. Moreover, some samples from both former and new sediment disposal sites exhibited toxicity. Therefore, results showed that sediments from the studied areas present evidences of degradation; however, further studies are required to determine relationships between toxicity and contamination. Results also suggested that the disposal of dredged sediments should be re-evaluated.